Effect of Polyherbal Drug Majun Falasfa on the Transgenic Drosophila Model of Parkinson’s Disease - Siddique, Yasir H.; Naz, Falaq; Rashid, Mohammad (Current Traditional Medicine, 2021)
Aim: The effect of Majun Falasfa (MF) was studied on the transgenic Drosophila expressing human alpha synuclein panneurally. Background: MF is a Unani medicine used for enhancing mental power and treating kidney, joint pains and urinary tract diseases. It is also used for phlegmatic diseases. It is also being used in age related dementia and to counter the effects of ageing. Methods: The equivalents of recommended dose for human were established for 20g of fly food i.e. 0.0014, 0.0028, 0.0042 and 0.0056g per 20g of diet. The PD flies were allowed to feed on it for 24 days before studying its effect on cognitive and oxidative stress parameters. Immuno-histochemistry was also performed to study the effect of MF on human alpha synuclein expression. Results: The exposure to MF increased the life span and improved the activity of PD flies. MF delayed the loss of climbing ability of PD flies. The exposure of PD flies to MF significantly reduced the oxidative stress and improves the antioxidant enzymes homeostasis compared to unexposed PD flies. The exposure to MF reduces the formation of Lewy bodies as is evident by immunohistochemistry. Conclusion: MF is potent in reducing the PD (Parkinson’s disease) symptoms being mimicked in the transgenic flies.
Keywords: Majun falasfa